Wild and Captive Environments Drive the Convergence of Gut Microbiota and Impact Health in Threatened Equids - Zhou, Zhichao; Tang, Liping; Yan, Liping; Jia, Huiping; Xiong, Yu; Shang, Jin; Shao, Changliang; Zhang, Qiangwei; Wang, Hongjun; He, Lun; Hu, Defu; Zhang, Dong (Frontiers in Microbiology, 2022)
To explore how the living environment influences the establishment of gut microbiota in different species, as well as the extent to which changes in the living environment caused by captive breeding affect wildlife’s gut microbiota and health, we used 16S rRNA gene amplicon sequencing and shotgun metagenomic sequencing to compare the gut microbiome of two species of threatened equids, the Przewalski’s Horse and the Asian wild ass, in the wild and captivity. The results revealed that different species of Equidae living in the same environment showed remarkable convergence of gut microflora. At the same time, captive populations exhibited significantly “unhealthy” microbiota, such as low Alpha diversity, high levels of potentially pathogenic bacteria and biomarkers of physical or psychological disease, and enrichment of microbial functions associated with exogenous exposure and susceptibility, implying that the artificial environment created by captivity may adversely impact the health of wildlife to some extent. Our findings demonstrate the importance of the environmental factors for the establishment of gut microbiota and host health and provide new insights into the conservation of wildlife in captivity from the perspective of the microbiome.